2017
DOI: 10.3389/fncir.2017.00047
|View full text |Cite
|
Sign up to set email alerts
|

Focal Stroke in the Developing Rat Motor Cortex Induces Age- and Experience-Dependent Maladaptive Plasticity of Corticospinal System

Abstract: Motor system development is characterized by an activity-dependent competition between ipsilateral and contralateral corticospinal tracts (CST). Clinical evidence suggests that age is crucial for developmental stroke outcome, with early lesions inducing a “maladaptive” strengthening of ipsilateral projections from the healthy hemisphere and worse motor impairment. Here, we investigated in developing rats the relation between lesion timing, motor outcome and CST remodeling pattern. We induced a focal ischemia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…The hSYN promoter resulted in neuron-specific transgene expression and this corroborated previous studies using this promoter [21,33,[52][53][54][55][56][57]. One study reported that the synapsin promoter is the most selective promoter among five neuron-specific promoters that were tested in the rat brain [56].…”
Section: Comparison Of Four Promoters For Transgene Expressionsupporting
confidence: 80%
See 1 more Smart Citation
“…The hSYN promoter resulted in neuron-specific transgene expression and this corroborated previous studies using this promoter [21,33,[52][53][54][55][56][57]. One study reported that the synapsin promoter is the most selective promoter among five neuron-specific promoters that were tested in the rat brain [56].…”
Section: Comparison Of Four Promoters For Transgene Expressionsupporting
confidence: 80%
“…The AAV1 serotype is commonly used to transduce the CST via intracortical injections [31][32][33][34][35][36][37][38]. An earlier study that compared seven AAV serotypes (AAV1-AAV6, and AAV8) identified AAV1 and AAV5 as the best and secondbest serotypes to transduce the CST in rats [20].…”
Section: The Aav1 Serotype For Transduction Of the Corticospinal Tracmentioning
confidence: 99%
“…3b,c ). To better analyze sensorimotor coordination, we also evaluated IE rats in the vertical ladder climbing 60 . This motor-specific test showed that IE rats require significantly more time to reach the top surface of the ladder in comparison to SC animals, confirming the general impairment of motor abilities (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, current knowledge recognizes, as main components of developmental neuroplasticity following perinatal brain injury, both influences of contralateral and ipsilateral corticospinal projections to the paretic hand, and the intrahemispheric and interhemispheric connections of the lesioned and intact motor cortices. It follows that the damaged as well as the intact motor cortex may represent potential central therapeutic targets for tDCS in UCP [9, 15, 16]. It is also important to consider that this neuromodulation tool can modulate the activity and functional connectivity of large-scale brain networks in both hemispheres, even when the stimulating electrode is applied “unilaterally,” over a specific cortical region, such as M1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…It follows that the damaged as well as the intact motor cortex may represent potential central therapeutic targets for tDCS in UCP [9, 15, 16]. It is also important to consider that this neuromodulation tool can modulate the activity and functional connectivity of large-scale brain networks in both hemispheres, even when the stimulating electrode is applied “unilaterally,” over a specific cortical region, such as M1 [15].…”
Section: Introductionmentioning
confidence: 99%